2012
DOI: 10.1093/neuonc/nos142
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, treatment and survival of patients with craniopharyngioma in the surveillance, epidemiology and end results program

Abstract: Craniopharyngioma is a rare primary central nervous system neoplasm. Our objective was to determine factors associated with incidence, treatment, and survival of craniopharyngiomas in the United States. We used the surveillance, epidemiology and end results program (SEER) database to identify patients who received a diagnosis of craniopharyngioma during 2004-2008. We analyzed clinical and demographic information, including age, race, sex, tumor histology, and treatment. Age-adjusted incidence rates and age, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 37 publications
6
86
1
4
Order By: Relevance
“…While one large population-based study demonstrated an association between subtotal resection and prolonged survival, reduced recurrence rates are generally associated with achievement of GTR in the reported literature. 11,[31][32][33]38 In the present series, we sought to directly compare outcomes of patients with lesions ultimately resected via either a pterional or EEA route at a center experienced in both skull base approaches. To reduce the selection bias inherently limiting retrospective review, cases fitting strict anatomical criteria were presented to 4 blinded neurosurgeons who had to exhibit equipoise, from the perspectives of accessibility, ability to achieve GTR, and knowledge of predicted morbidity, prior to case inclusion into the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While one large population-based study demonstrated an association between subtotal resection and prolonged survival, reduced recurrence rates are generally associated with achievement of GTR in the reported literature. 11,[31][32][33]38 In the present series, we sought to directly compare outcomes of patients with lesions ultimately resected via either a pterional or EEA route at a center experienced in both skull base approaches. To reduce the selection bias inherently limiting retrospective review, cases fitting strict anatomical criteria were presented to 4 blinded neurosurgeons who had to exhibit equipoise, from the perspectives of accessibility, ability to achieve GTR, and knowledge of predicted morbidity, prior to case inclusion into the study.…”
Section: Discussionmentioning
confidence: 99%
“…16 With an incidence of 0.2/100,000 and a frequently benign histology, these tumors are a challenging neurosurgical disease with a 3-year relative survival of 88%. 38 Invasive components make resection technically challenging and associated with potential morbidity. These tumors also frequently recur after resection or adjuvant therapy, and frequently result in neurological deficits, with common presenting symptoms including hypopituitarism, cognitive dysfunction, and visual impairment.…”
mentioning
confidence: 99%
“…While considerable literature compares the merits and limitations of initial GTR versus STR and external beam radiation as the mainstays of initial therapy [5,919], alternative algorithms including intracystic therapies [2026], progression contingent radiation [27], and stereotactic radiosurgery [2831] have also been well described through both primary and secondary data analyses [7,8,32,33]. This survey intended to expand on recent secondary data analyses by assessing how commonly alternative algorithms are employed by contemporary neurosurgeons.…”
Section: Discussionmentioning
confidence: 99%
“…While the most commonly described algorithm centers around the choice between Gross Total Resection (GTR) and Subtotal Resection (STR) augmented by external beam radiation (RT), multiple groups promote an individually tailored treatment approach [16]. Two recent analyses of the National Cancer Institute’s Surveillance, Epidemiology and End Results (SEER) datasets indicate that a significant portion of patients in the United States are not initially treated with GTR or STR + RT [7,8]. While alternative therapeutic regimens, such as intracystic therapy or progression contingent radiation are well established, these data prompted us to further explore the initial practice patterns of neurosurgeons using a brief survey.…”
Section: Introductionmentioning
confidence: 99%
“…Nie wykazano przewagi żadnej płci. Rasę czarną charakteryzowała większa zapadalność w stosunku do rasy białej, odpowiednio 2,1 do 1,7/mln/rok [34].…”
Section: Streszczenieunclassified